Antidiabetic Potential of Ethanol Extract from Moringa oleifera Leaves in Streptozotocin-Nicotinamide-Induced Female Mus musculus - Vinsa Cantya Prakasita; Nadya Aprina Theodora; Enjelin Anjung Susilowati; Dwi Aditiyarini; Aniek Prasetyaningsih (Jurnal Biodjati, 2024)
Type 2 diabetes mellitus (DM) is a chronic metabolic disorder characterized by elevated blood glucose levels due to insulin resistance. Type 2 diabetes is considerably more prevalent than other forms (85–90%). The risk of type 2 diabetes is higher in women (53.2%). There is an urgent requirement for better and more affordable treatment options considering DM therapy is expensive and may have adverse health effects. The study's objective is to examine how acute toxicity, blood glucose levels, and body weight are affected by Moringa leaf ethanol extract (MLEE). Maceration was employed to eliminate the leaves of the moringa plant. Phytochemical screening was completed to assess the total flavonoid content and screen for alkaloids, flavonoids, phenolics, saponins, and tannins. Acute toxicity testing was performed following OECD guideline 423. Clinical symptoms of acute toxicity were observed every 30 minutes for the first 24 hours post-treatment, followed by observations every 24 hours up to 14 days. The estimated LD50 range was determined. Streptozotocin/ nicotinamide-induced female Mus musculus was administered to evaluate the antidiabetic potential of MLEE. Six groups of mice were utilized, which included a healthy control group (aquades not induced), a negative control group (induced aquades), a positive control group (induced glimepiride 0.8 mg/kg BW), and three treatment groups with varying dosages of MLEE (induced; 0, 100, and 150 mg/kg BW). A semi-auto chemical analyzer was employed on days 0 through 31 to determine blood glucose levels. An analytical digital balance was utilized to calculate the body weight. With a total flavonoid concentration of 20.75%, MLEE incorporated alkaloids, flavonoids, phenolics, saponins, and tannins. MLEE demonstrated a significant effect in lowering blood glucose levels at a dose of 100 mg/kg BW (P<0.05). A significant positive correlation has been identified between body weight and blood glucose levels (P<0.05).